2020
DOI: 10.1136/jmedgenet-2019-106525
|View full text |Cite
|
Sign up to set email alerts
|

Xq28 copy number gain causing moyamoya disease and a novel moyamoya syndrome

Abstract: BackgroundThe molecular anomalies causing moyamoya disease (MMD) and moyamoya syndromes (MMS) are unknown in most patients.ObjectiveThis study aimed to identify de novo candidate copy number variants (CNVs) in patients with moyamoya.MethodsRare de novo CNVs screening was performed in 13 moyamoya angiopathy trios using whole exome sequencing (WES) reads depth data and whole genome high density SNP array data. WES and SNP array data from an additional cohort of 115 unrelated moyamoya probands were used to search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…3) [38]. It has a higher incidence in Japan and Korea, probably due to founder mutations [39][40][41][42]. Histopathological studies have shown that pathophysiological pathways of European and Asian MA seem identical despite different genetic predispositions [43].…”
Section: Moyamoya Angiopathymentioning
confidence: 99%
“…3) [38]. It has a higher incidence in Japan and Korea, probably due to founder mutations [39][40][41][42]. Histopathological studies have shown that pathophysiological pathways of European and Asian MA seem identical despite different genetic predispositions [43].…”
Section: Moyamoya Angiopathymentioning
confidence: 99%
“…( 8 ). Some studies have indicated the importance of investigating the effect of pathways of interest on the occurrence and development of MMD ( 14 16 ). However, information regarding the significantly different methylation sites in adult ischemic MMD remains scarce.…”
Section: Discussionmentioning
confidence: 99%
“…The research group has demonstrated a new Xq28 CNV gain in both MMA and a novel MMS related to pulmonary vein stenosis, pulmonary hypertension, and other distinct systemic venous anomalies. These data may be relevant for clinical care and genetic counseling (319). MMA patients may present with a significantly increased rate of persistent carotidvertebrobasilar anastomoses compared to controls (320), and may be 26 times more likely to suffer from Down's syndrome (321, 322).…”
Section: Moyamoya Angiopathy Moyamoya Syndrome and Inflammationmentioning
confidence: 99%